Reação do tecido conjuntivo subcutâneo de ratos ao implante de Artglass®: estudo histológico - Marinho, Márcio Von Dreiffus [UNESP]; Kusuda, Ricardo; Okamoto, Roberta [UNESP]; Okamoto, Tetuo [UNESP]; Felipini, Renata Calestini [UNESP]; Alves-Rezende, Luís Guilherme Rosifini; Alves-Claro, Ana Paula Rosifini [UNESP]; Rezende, Maria Cristina Rosifini Alves [UNESP] (My University, 2010)
Indirect composite resin systems have been routinely recommended for making restorations in distressed patients. The purpose of this study was to evaluate histologically in rats the effect of chronic stress on the reaction of subcutaneous connective tissue after implant of Artglass™. For this purpose, 60 rats were divided into four groups (GI (control), GII (stressed), GIII (Artglass™) and GIV (Artglass™. / stressed) received dorsal subcutaneous implants of polyethylene tubes containing saline solution (GI and GII) or Artglass™ (GIII and GIV). In groups of four animals were sacrificed at 7,14 and 28 days postoperatively. The results allowed to observe more intense inflammatory reaction and tissue organization later in the animals subjected to stress.

Sistemas indiretos de resina composta têm sido rotineiramente indicados para confecção de restaurações em pacientes estressados. O propósito deste trabalho foi estudar histologicamente em ratos o efeito do estresse crônico sobre a reação do tecido conjuntivo subcutâneo ao implante de Artglass®. Para tanto, 60 ratos, divididos em quatro grupos (GI (controle), GII (estressado), GIII (Artglass®) e GIV (Artglass®/Estressado) receberam implante subcutâneo, bilateral e dorsal, de tubos de polietileno contendo soro fisiológico (Grupos I e II) ou Artglass® (Grupos III e IV). Em grupos de cinco, os animais foram sacrificados aos 7,14 e 28 dias pós-operatórios. Os resultados obtidos permitiram observar reação inflamatória mais intensa e organização do tecido conjuntivo mais tardia nos animais submetidos ao estresse.
Reaction of the subcutaneous tissue of rats to Artglass®: histological study
Keywords: Wound healing; Hypothalamohypophyseal system; Pituitary-adrenal system; Ceromer; Cicatrização de feridas; Sistema hipotálamo-hipofisário; Sistema hipófisesupra-renal; Cerômero